Anthraquinones from Morinda elliptica - Ismail, Nor Hadiani; Ali, Abdul Manaf; Aimi, Norio; Kitajima, Mariko; Takayama, Hiromitsu; Lajis, Md. Nordin (Elsevier Science, 1997)
Phytochemical studies on roots of Morinda elliptica have resulted in the isolation of a new anthraquinone, 2-formyl-1-hydroxyanthraquinone, and 10 known anthraquinones. The structures of the anthraquinones were established based on spectral studies.